Cellular cross talk, inflammatory signals, and enhanced microvascular permeability. (April 2017) - Breslin, Jerome W.
Abstract: Microvascular leakage remains a significant clinical problem for which there is no specific therapeutic available. This Special Topics issue of the journal Microcirculation features reviews pertaining to the cellular and molecular mechanisms that control the integrity of the microvascular barrier. (Meegan et al., Microcirculation, 2017) summarize recent research findings about how neutrophil extracellular traps and how these can cause injury to the microvascular barrier.( Zhang et al. Microcirculation, 2017) highlight the microvascular response to advanced glycation end‐products that are formed as part of the pathophysiology of diabetes mellitus. These ongoing investigations are helping to clarify the mechanisms by which endothelial cells receive information and integrate it to generate cellular responses that fine‐tune barrier function. Better understanding of these mechanisms is needed for the rational development of therapeutic strategies to reduce excessive microvascular leakage.